Preparedness of Coastal Community Purworejo Against Megatrhtust Threat - Abdul Latief RF; Chatarina Muryani; Yasin Yusup (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
Since the tsunami in 2004 in the Indian Ocean, studies of the megatrust tsunami have been increasing. One of the reasons is because the megatrust tsunami can cause large numbers of casualties, as has happened in Aceh and Mentawai (Indonesia). The threat of a megatrust tsunami now stretches along the coastline of the southern island of Java. Communities who are in the southern part of Java, ideally have the ability to be prepared to face a tsunami disaster. Therefore, an assessment of community preparedness in the face of a tsunami in Purworejo Regency is an urgency, because Purworejo is one of the regencies directly adjacent to the ocean in the south of Java Island. This study uses a combination of questionnaires, interviews, observation and documentation to obtain data. This study provides information on the classification of villages along the coast of Purworejo in relation to the level of preparedness to face the threat of a tsunami disaster. The result is that from 16 villages 2 of them are of high status, 2 are low and the rest are moderate.